2016
DOI: 10.1186/s12896-016-0273-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel strong promoter of antimicrobial peptides gene pro-SmAMP2 from chickweed (Stellaria media)

Abstract: BackgroundIn a previous study we found that in chickweed the expression level of the pro-SmAMP2 gene was comparable or even higher to that of the β-actin gene. This high level of the gene expression has attracted our attention as an opportunity for the identification of novel strong promoters of plant origin, which could find its application in plant biotechnology. Therefore, in the present study we focused on the nucleotide sequence identification and the functional characteristics of the pro-SmAMP2 promoter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The extracts significantly inhibited the microbial growth of the gram positive and negative bacteria [45]. In a recent study, peptides genepro-SmAMP2 and β-actin gene isolated from S. media significantly displayed strong inhibitory activity against the tested bacterial isolates whereas Sm-AMP-X exhibited significant inhibitory activity against phytopathogenic fungi due to the N-and C-terminal regions of the specified peptide [46,47]. 2.9.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The extracts significantly inhibited the microbial growth of the gram positive and negative bacteria [45]. In a recent study, peptides genepro-SmAMP2 and β-actin gene isolated from S. media significantly displayed strong inhibitory activity against the tested bacterial isolates whereas Sm-AMP-X exhibited significant inhibitory activity against phytopathogenic fungi due to the N-and C-terminal regions of the specified peptide [46,47]. 2.9.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The strains were injected into leaves with a needle-free syringe. Agrobacterial transformation of plants was performed by the "lawn" method, which had been used earlier (Komakhin et al, 2016). Genetic constructs for transient expression containing the reporter gene gus controlled by the plant promoters were incorporated into plasmid pCambia1381Z (Cambia, Australia).…”
Section: Methodsmentioning
confidence: 99%
“…At the present time in plant biotechnology there is a deficit of regulatory elements for effective expression of recombinant genes due, first, to the lack of native promoters of plant genes with necessary parameters (Naqvi et al, 2010) and, secondly, to complexity in using available promoters for coordinated transcriptional control (Shrestha et al, 2018). We had previously found that hevein-like peptide genes from chickweed (Stellaria media) are a source of strong constitutive promoters for biotechnology of cultivated plants (Shukurov et al, 2012;Komakhin et al, 2016;Vysotskii et al, 2016;Vetchinkina et al, 2016). E. g., in transient expression experiments in Nicotiana benthamiana pro-SmAMP1 and pro-SmAMP2 promoters were 2-4 times more effective than the CaMV35S promoter; in rape (Brassica napus) and sugar beet (Beta vulgaris) plants pro-SmAMP1 and pro-SmAMP2 were comparable to CaMV35S (Madzharova et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Curiously, only for cultivated cereals were these peptides obtained first. It allowed a reconsideration of the modern classification of hevein AMPs to diverge them into two subfamilies: six-cysteine-containing peptides, such as peptides from amaranth ( Amaranthus caudatus, A. retroflexus ) [ 73 , 74 , 75 ], common chickweed ( Stellaria media ) [ 76 , 77 ], and 10-cysteine-containing peptides [ 78 , 79 ]. The most famous examples are wheat antimicrobial peptides (WAMPs) from T. kiharae and lyme grass antimicrobial peptides (LAMP) from L. arenarius families [ 80 , 81 ].…”
Section: Investigation Of Structural Determinants Of Other Amps (Tmentioning
confidence: 99%